Injection drug use, food insecurity, and HIV-HCV co-infection: a longitudinal cohort analysis. Issue 10 (3rd October 2018) - McLinden, Taylor; Moodie, Erica E. M.; Harper, Sam; Hamelin, Anne-Marie; Anema, Aranka; Aibibula, Wusiman; Klein, Marina B.; Cox, Joseph
ABSTRACT: Injection drug use (IDU) and food insecurity (FI) are highly prevalent among individuals living with HIV-hepatitis C virus (HCV) co-infection. We quantified the association between IDU and FI among co-infected individuals using biannual data from the Canadian Co-infection Cohort ( N  = 608, 2012–2015). IDU (in the past six months) and IDU frequency (non-weekly/weekly in the past month) were self-reported. FI (in the past six months) and FI severity (marginal FI, moderate FI, and severe FI) were measured using the Household Food Security Survey Module. Generalized estimating equations were used to estimate risk ratios (RR) quantifying the associations between IDU, IDU frequency, and FI with Poisson regression. The associations between IDU, IDU frequency, and FI severity were quantified by relative-risk ratios (RRR) estimated with multinomial regression. At the first time-point in the analytical sample, 54% of participants experienced FI in the past six months, 31% engaged in IDU in the six months preceding the FI measure, and 24% injected drugs in the past month. After adjustment for confounding, IDU in the past six months (RR = 1.15, 95% confidence interval [CI] = 1.04–1.28) as well as non-weekly (RR = 1.15, 95% CI = 1.02–1.29) and weekly IDU (RR = 1.21, 95% CI = 1.07–1.37) in the past month are associated with FI. Weekly IDU in the past month is also strongly associated with severe FI (RRR = 2.68, 95% CI = 1.47–4.91). Our findings indicate that there is an association between IDU and FI, particularly weekly IDU and severe FI. This suggests that reductions in IDU may mitigate FI, especially severe FI, in this vulnerable subset of the HIV-positive population.